Proses Pembuatan Baja Ringan Di CV. Muara Nusantara - Muhamad Ariq Firdian (Peneliti.net, 2023)
Production produced by CV. Muara Nusantara is mild steel. Mild steel is one of the basic materials for making roofs to protect against erratic weather such as hot and cold conditions. Based on the situation in the CV. Muara Nusantara, it is important to study the production flow chart on CV. Archipelago. The flowchart that is in production at CV. Muara Nusantara is useful for making the production flow easier and faster so that the production process is not too long and in accordance with the desired target. The production process for making mild steel carried out at CV. Muara Nusantara is a stock store (safety stock). There are 2 types of machines used in the mild steel production process, namely forming machines and cutting machines. stock). There are 2 types of machines used in the mild steel production process, namely forming machines and cutting machines. The type of process flow used in CV. Muara Nusantara is of the u-shape type which can be seen from the flow chart, the very large area, the placement of the machine and also each division in the light steel production process.